Preparation, Characterization And Evaluation Of Mesoporous Activated Carbons Derived From Agricultural By-Products For Adsorption Of Methylene Blue And 2,4,6- Trichlorophenol [TD420. T161 2008 f rb]. - Tan, Ivy Ai Wei (2008)

(untitled)
Penggunaan secara meluas karbon teraktif komersil dihadkan oleh kos yang tinggi disebabkan oleh penggunaan bahan mentah yang tidak dapat diperbaharui.